Novos inimigos das formigas lava-pé (complexo Solenopsis saevissima (Hymenoptera: Formicidae). - Williams, Roger N.; Whitcomb, Willard H. (Anais da Sociedade Entomológica do Brasil, 1973)
During the pst tvo years studies vete conducted in Mato Grosso and São Paulo to determine the insect natural enemies of fite ants ia the Solenopsis saevissima complex. Thus far these studies have yielded 6 species of Pseudacteon ( Phori-dae), a new parasitic Apodicrania (Phoridae), one new parasite wasp, Orasema (Eucharitidae) and a new temporary social parasire, Solenopsis (Formicidae). Methods of collecting vete as follows: (1) placing an inverted vial over enemy vhileflying above fite ant vorlrera or resting on soil surface; (2) inundatang nest contents slowly ia a talced bucket; and (3) opening nest to verify presence of small gunes (Salenopsis). Notes on the biology and bebavior of the parasitic species are given along with a discussion of parasite-host relationships.